PERAN DAN KONTRIBUSI PEREMPUAN DALAM INDUSTRI NUKLIR DI INDONESIA: STUDI KASUS LULUSAN PERGURUAN TINGGI VOKASI NUKLIR - Ahsanti Adiba Rahma (PT. Hasba Edukasi Mandiri, 2025)
Women's participation in STEM (Science, Technology, Engineering, and Mathematics), including the nuclear sector, remains globally low despite gradual improvements driven by various support initiatives. The Polytechnic Institute of Nuclear Technology of Indonesia, as the only vocational higher education institution in nuclear studies in the country, plays a crucial role in producing competent human resources for the nuclear sector, including female professionals. This study employs literature review and questionnaire surveys to explore women’s perceptions of the challenges and opportunities in pursuing careers in the nuclear sector. Survey results show that 45.2% of respondents chose to study at the Polytechnic Institute of Nuclear Technology of Indonesia due to job opportunities in the nuclear sector, indicating growing awareness among women of career prospects in this field. Data from the past five years (2020–2024) shows that out of 438 graduates, 161 (36.75%) were women, with 32.9% of them currently working in the nuclear field. The survey also reveals that the institution provides significant support in career preparation and development, especially for female students: 53.2% of respondents agreed that the institution supports women’s involvement in the nuclear sector, and 21% rated this support as highly significant. However, technical and practical challenges remain key barriers for women in this field, as indicated by 64.5% of respondents. Other challenges include heavy academic workloads and the lack of female representation in the nuclear sector. As a result, respondents highlighted the importance of equipping students with technical competencies and relevant skills prior to entering the workforce. This study affirms that a vocational institution focused on nuclear education can increase the number of women in the nuclear sector while also reducing gender stereotypes that have long hindered their participation. Furthermore, 45.2% of respondents reported being fairly satisfied, and 43.5% satisfied, with the training provided by the institution. However, 64.5% expressed a need for more advanced technical and professional training, especially for women, to further encourage female careers in the nuclear field. This study concludes that while women remain underrepresented in the nuclear industry, there is significant potential to increase their participation through policy support, improved educational facilities, and the involvement of women's communities in nuclear career promotion. These findings are expected to serve as a reference in developing sustainable workforce strategies and enhancing inclusivity in the nuclear sector, thereby contributing to a more diverse and competitive nuclear industry in Indonesia.